2011
DOI: 10.1080/00103624.2011.602451
|View full text |Cite
|
Sign up to set email alerts
|

Improving Phosphorus Use through Co-inoculation of Vesicular Arbuscular Mycorrhizal Fungi and Phosphate-Solubilizing Bacteria in Maize in an Acidic Alfisol

Abstract: Performance of three vesicular arbuscular mycorrhizal (VAM) fungi cultures and a phosphate-solubilizing bacteria (PSB) culture alone or in combination with or without 75% of the recommended P 2 O 5 dose based on soil-test crop response model was examined in maize in a phosphorus (P)-deficient acidic Alfisol in a glasshouse pot experiment. Sole application of VAM besides co-inoculation with PSB (Pseudomonas striata) and inorganic P stimulated mycorrhizal root colonization. Sole application of PSB, VAM T (Glomus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Phosphate solubilizing microorganisms can enhance plant growth through several different mechanisms in addition to providing available phosphorus to plants (Mundra et al, 2011). Several researchers have reported that synergistic interaction between bacteria and fungi (Bras and Nahas, 2012;Suri et al, 2011). Suri et al (2011) observed synergistic interaction between Arbuscular Mycorrhizal Fungi (AMF) and Phosphate-Solubilizing Bacteria when co-inoculated to Maize plant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphate solubilizing microorganisms can enhance plant growth through several different mechanisms in addition to providing available phosphorus to plants (Mundra et al, 2011). Several researchers have reported that synergistic interaction between bacteria and fungi (Bras and Nahas, 2012;Suri et al, 2011). Suri et al (2011) observed synergistic interaction between Arbuscular Mycorrhizal Fungi (AMF) and Phosphate-Solubilizing Bacteria when co-inoculated to Maize plant.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have reported that synergistic interaction between bacteria and fungi (Bras and Nahas, 2012;Suri et al, 2011). Suri et al (2011) observed synergistic interaction between Arbuscular Mycorrhizal Fungi (AMF) and Phosphate-Solubilizing Bacteria when co-inoculated to Maize plant.…”
Section: Resultsmentioning
confidence: 99%
“…Soybean root system also revealed the superiority of VAM T (Glomus intraradices) and VAM I (Glomus mosseae) cultures over the local VAM (Glomus mosseae) culture with respect to root infectivity in an acidic Alfisol. Coinoculation of VAM and phosphatesolubilizing bacteria (PSB) cultures further improved the root colonization in soybean, indicating that there exists a synergistic interaction between VAM and PSB (Sreenivasa and Krishnaraj 1992;Suri et al 2011a). Gryndler et al (1990) and Singh and Singh (1993) have also reported similar results in maize and soybean crops.…”
Section: Root Infectivity and Root Biomassmentioning
confidence: 97%
“…In this context, dual inoculation of VAM and PSB might be useful in reversing the process of P fixation in an acidic Alfisol (Suri et al 2006), as VAM will largely mobilize available P by increasing the surface area of roots and greater exploration of soil volume by its hyphal network, leading to greater nutrient-use efficiency (George et al 1992;Suri et al 2011b) and PSB will solubilize insoluble phosphates to some extent (Suri et al 2011a). In the light of these facts, a greenhouse pot experiment was conducted to study the GlycineGlomus-PSB interactions in soybean using a local PSB culture and three VAM cultures, individually and in combination with PSB.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation